REKAYASA BIOPROSES PRODUKSI BIOETANOL DARI UBI KAYU DENGAN TEKNIK KO-KULTUR RAGI TAPE DAN SACCHAROMYCES CEREVISIAE - IWayan Arnata; A A M Dewi Anggreni (AGROINTEK, 2013)
The purpose of this study is to get an alternative bioprocess technology of bioethanolproduction from cassava using the technique of co-cultured “tape” yeast and Saccharomycescerevisiae. The study was designed with a completely randomized design experiment using 7level of co-culture techniques. All treatment was repeated 2 times. The parameters measuredwere the final pH, percentage of substrate consumption, ethanol concentration and fermentationefficiency. Using coculture technique in the process of fermentation to producebioethanol gives better results than the use of a single culture or pure culture of “tape”yeast and S. cerevisiae. Coculture technique that gives the best results is the treatmentof fermentation process by giving the “tape” yeast to the first day and followed bygiving culture S. cerevisiae for the next two days. This treatment has a final pH 4:05,the percentage substrate or glucose consumption of 82.92%, the concentration ethanolof 11.0% (w/v) and the fermentation efficiency of 52.94%.